Alcohol Use Disorder: An Interprofessional Case-Based Exercise - Robin English; Scott Edwards; Megan Armstrong; Kathleen McDonough; Patricia Molina (Association of American Medical Colleges, 2014)
Abstract Introduction This case was developed for an interprofessional education elective at our institution. The goal of that course is to allow students from various health sciences schools to learn with, from, and about each other in the context of patient care. One component is a set of small-group case discussions that focus on each health care profession's role in and contribution to patient care. Cases developed for the course are designed to be sufficiently complex as to require input from multiple health care professions. Methods This resource is the case of a man with alcohol use disorder (AUD) presenting to a multidisciplinary clinic for care after an alcohol-related injury. The case was designed to help students recognize AUD in patients and clients and to facilitate their development of an interprofessional care plan. The resource includes a detailed faculty facilitation guide, which was designed to help students consider their own roles and recognize the roles of other health care providers in patient care, as well as case details for students, additional AUD information for facilitators, and a bibliography. Students were given online access to prereading on AUD, provided with the initial information for the case, and asked to prepare their responses to the initial questions before coming to class. To assess the effectiveness of the case in helping students achieve the learning objectives, an online pretest survey was administered to students. The same survey was delivered on paper after the case discussion. The final component of the session was a demonstration of the Alcohol Use Disorder Identification Test (AUDIT) with a simulated patient. Results Analysis of the results of pre- and postcase discussion surveys showed that after the case discussions, students were better able to identify the AUDIT as a useful screening tool, recognize binge drinking patterns, and identify biomedical consequences of AUD. A debriefing with faculty facilitators revealed that they felt that student learning had occurred, the discussions had focused on interprofessional aspects, and the case should be utilized again in future offerings of the course. Discussion Users are encouraged to solicit input from various health care providers in their own institutions to further expand the section with additional information on AUD. We identify two limitations to use of this case. First, the success of small-group case discussions depends largely on the skill of the facilitator and, to a smaller degree, on the facilitator's clinical expertise. Different groups may have different discussions despite our providing facilitators with discussion guides. As long as the interprofessional aspects of care are emphasized, this is acceptable. Second, use of this case assumes that students have read the assigned articles ahead of time. Failure to do so will result in significantly diminished contributions from students. This can be addressed by emphasizing the importance of preparation and including some assessment of the students' apparent preparation in their evaluations.